Fixed-point time-periodic FEM taking into account hysteresis characteristics of laminated core under DC bias - Wang, Shuaibing; Li, Lin; Zhao, Xiaojun; Xie, Yuqing (International journal of applied electromagnetics and mechanics, 2017)
The special hysteresis characteristics of the laminated core (LC) under DC bias are analyzed and the hysteresis loops are simulated by the hysteresis model based on consuming function. The field-circuit coupled time-periodic FEM (TPFEM) combined with the locally convergent fixed-point method is presented to calculate the excitation current and magnetic field of LC under DC bias. A method by increasing the resistance and setting up a compensation voltage artificially is proposed in this paper, which can solve the stability problems caused by the lack of convergence of solutions when the DC-biased condition becomes more serious. Besides, the excitation current of LC with no-load and different loads under DC bias is analyzed based on the field-circuit coupled fixed-point TPFEM.